EFFECTIVE MANAGEMENT OF WORKING CAPITAL IN DOMESTIC COMPANIES: METHODS AND PRACTICAL RECOMMENDATIONS - Khamitova Zh. A.; Dzholdybayeva A. N.; Serikbaev E.; Kupeshova B.K. (Research Retrieval and Academic Letters, 2024)
Currently, Working capital management is becoming a key aspect of financial strategy for enterprises in a rapidly changing economic environment. This text examines the relevance of the problem of working capital management in modern business, the specifics of its optimization and the impact on the financial condition of companies. In a rapidly changing economic environment, effective working capital management is becoming a key element of an enterprise’s financial strategy. Optimized inventory levels prevent cost overruns and reduce the risk of product obsolescence. Effective management of accounts receivable and accounts payable affects liquidity and ensures a stable financial condition. In addition, in the context of globalization and accelerated pace of technological development, companies face increasing uncertainty. Skillful working capital management allows enterprises to flexibly and adapt to changing market conditions, reducing financial risks and ensuring stability. Using the example of three large domestic companies - Kazchrome, KazMunaiGas and KEGOC, various aspects of working capital management are studied, including accounting for cash, receivables and payables, inventories and the time value of finished products. The paper also provides a comparative analysis of the effectiveness of working capital management in these companies over the past three years.